Assessing the intersection/remagnetization puzzle with synthetic apparent polar wander paths. Issue 2 (28th May 2018) - Pivarunas, Anthony F; Meert, Joseph G; Miller, Scott R
SUMMARY: Palaeomagnetic data are of variable quality. To assist in a systematic assessment of data, a set of seven quality criteria (VQ1–VQ7) were introduced by Van der Voo. The last of those criteria 'VQ7' concerns the possibility of remagnetization when a particular palaeomagnetic pole resembles a younger palaeopole from the same stable region. While remagnetizations are often the culprit, the mere resemblance of an older pole to a younger pole does not a priori require that the rocks under investigation are remagnetized. Given that the Earth has a finite surface area, that apparent polar wander paths (APWPs) are represented as wide swathes rather than points, and that continental motion has taken place over several billion years, we ask the question 'How likely is it for an APWP to loop back on itself?' To answer this question, we constructed synthetic APWPs in an effort to evaluate the likelihood of self-intersection. We find that given 500 Myr of apparent polar wander, ∼60 per cent of the synthetic APWPs show self-intersection. Given 1000 Myr of apparent polar wander, ∼95 per cent of the synthetic APWPs show self-intersection. These results show that resemblance to younger palaeopoles, over the long term, may be governed by simple probability rather than only remagnetization. We recognize that remagnetization does occur, sometimes pervasively, and must be reckoned with in the assessment of palaeomagnetic data. Perhaps VQ7 should be amended to the first sentence in the original discussion, and focus on satisfying 'No suspicion of remagnetization' via other means rather than solely a resemblance to younger poles.